Racial Identity-Rooted Academic Motivation of First-Year African American Students Majoring in STEM at an HBCU - Freeman, Kimberley Edelin; Winston-Proctor, Cynthia Eileen; Gangloff-Bailey, Felicia; Jones, Jason M. (Frontiers in Psychology, 2021)
The purpose the present study is to explore African American undergraduate students’ perceptions of their experiences and academic motivation within a Historically Black College or University (HBCU) learning environment. As part of a larger study, we collected 212 open-ended survey responses from first year students in STEM majors about how the HBCU context shapes their academic motivation. We used semantic thematic data analysis and found three major themes and corresponding sub themes that were salient in the development of students’ academic motivation: place (institutional climate, HBCU mission and tradition, and absence of marginalization); pedagogy (culturally relevant pedagogy, positive faculty-student relationships, African American curriculum and instruction, racial socialization); and people (people “like me”; student, faculty and alumni models of high achieving African Americans). We discovered that HBCU institutional factors engendered academic motivation that is rooted in students’ racial identity and suggest the construct of racial identity-rooted academic motivation. Given the important and unique realities of African American students that impact their educational experiences, engagement, identity development, and achievement in various types of school contexts, self and sociocultural variables must be included in research and theory on the motivational psychology of African American students. Implications for higher education practice and future research are discussed.